2018
DOI: 10.1111/cea.13091
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal maternal psychosocial stress and offspring's asthma and allergic disease: A systematic review and meta‐analysis

Abstract: Exposure to prenatal maternal psychosocial stress was associated with increased risk, albeit modestly, of asthma and allergy in the offspring. The pronounced risk during the third trimester may represent cumulative stress exposure throughout pregnancy rather than trimester-specific effect. Our findings may represent a causal effect or a result of inherent biases in studies, particularly residual confounding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
127
1
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(146 citation statements)
references
References 58 publications
11
127
1
7
Order By: Relevance
“…Several studies suggested that children exposed to stress or mental health problems during pregnancy had an increased risk of wheezing and asthma; in most studies, the outcome was wheezing in pre‐schoolers . Our results on wheezing are consistent with those of Chiu et al that assessed the association of perinatal negative life events with offspring wheezing symptoms from birth to age 2 years.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Several studies suggested that children exposed to stress or mental health problems during pregnancy had an increased risk of wheezing and asthma; in most studies, the outcome was wheezing in pre‐schoolers . Our results on wheezing are consistent with those of Chiu et al that assessed the association of perinatal negative life events with offspring wheezing symptoms from birth to age 2 years.…”
Section: Discussionsupporting
confidence: 89%
“…There is consistent evidence that pre‐ and postnatal maternal stress is associated with mental health problems and negative health outcomes in children, especially developmental and psychologic disorders . Two recent meta‐analyses and one systematic review showed that prenatal psychologic stress is associated also with the risk of both asthma and wheezing . Types of stress indicators included experience of negative life events, doctor diagnosis of maternal anxiety and depression, and stress perception.…”
Section: Introductionmentioning
confidence: 99%
“…There is compelling evidence that children exposed to high levels of prenatal stress are at risk for a host of adverse health outcomes [1, 2, 3, 4, 5, 6, 7]. Prenatal maternal stress (PNMS) increases fetal exposure to stress biomarkers (e.g., cortisol and pro-inflammatory cytokines) and may alter the development of critical biological systems (e.g., the endocrine, immune, and nervous systems) [8, 9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…Prenatal maternal stress (PNMS) increases fetal exposure to stress biomarkers (e.g., cortisol and pro-inflammatory cytokines) and may alter the development of critical biological systems (e.g., the endocrine, immune, and nervous systems) [8, 9, 10]. This confers lasting susceptibility to health complications in the child [2, 4, 5, 6] and potentially transgenerational risks through epigenetic programming [8, 9, 11]. There is also accumulating evidence that the child’s biological sex may modify the effect of PNMS on child health [12, 13, 14, 15].…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Consequently, systematic reviews and meta-analysis are very powerful and Flanigan's elegant review on prenatal maternal psychosocial stress and offspring's asthma and allergic disease in this year's Clinical and Experimental Allergy addressed causality very well. 8 Findings that atopic diseases and depression or anxiety tend to occur together in families indicate a genetic explanation for comorbidity, although this was not supported in a large twin study by Brew et al 9 There may also be factors that modify the association between a risk factor and subsequent asthma or allergic disease. Reports from Isle of Wight have suggested that breastfeeding duration may modify the effect of smoking during pregnancy on eczema from early childhood to adolescence, 10 and in a Finnish birth cohort, the association between pet exposure and sensitization was modified by pollen exposure in early pregnancy.…”
Section: Antenatal Exposuresmentioning
confidence: 98%